Significance of social networks in communication with service users in modern catering industry - Božić Aleksandar; Zubanov Violeta (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Modern forms of communication are largely based on the use of the Internet, with great contribution of social networks to communication. Although social networks have become an integral part of everyday activities, their use in communication between restaurants and users of their services in Serbia has been little explored. Analyzing data about restaurants on six social networking websites (Facebook, Twitter, Instagram, Foursquare, Linkedin and Trip Advisor), research was done on the way these networks are used to communicate with service users. On all the analyzed networks, information about restaurants was found, with the contents and the way of communication being different between observed networks, which is expected due to their specificity. Also analysed was the presence of restaurants from different towns in Serbia on the Trip Advisor portal, confirming the positive correlation between the size of cities (area and population) and the number of restaurants visible on this portal. The SWOT analysis examined the advantages and disadvantages of using social networks in catering industry, where it was noted that there are considerably more advantages of this kind of communication. Also, it has been noted that there is a good chance to improve this communication, but this task should be approached with care and professionalism in order to avoid the unwanted effects of the use of social networks on the restaurant business.